Circulating methylated THBS1 DNAs as a novel marker for predicting peritoneal dissemination in gastric cancer. Issue 9 (13th August 2021) - Hu, Xuan‐Yu; Ling, Zhe‐Nan; Hong, Lian‐Lian; Yu, Qi‐Ming; Li, Pei; Ling, Zhi‐Qiang
Abstract: Objectives: Thrombospondin 1 ( THBS1) is known to play a key role in tumor metastasis, and aberrant DNA methylation is one of the mechanisms regulating THBS1 . The present study investigated whether methylated THBS1 in circulating cell‐free DNA from preoperative peritoneal lavage fluid (PPLF) and peripheral blood could be used as a potential biomarker for predicting peritoneal dissemination in gastric cancer (GC) patients. Methods: The status of THBS1 methylation was detected by quantitative methylation‐specific PCR (MSP) in tumor tissues, paired PPLF, and serum from 92 GC patients. The correlation between methylated THBS1 levels and peritoneal dissemination of GC was studied, and its diagnostic value for predicting peritoneal dissemination was clarified by the receiver operating characteristic (ROC) curve. Results: Aberrant THBS1 methylation in tumor tissues was significantly higher than that in paracancerous normal tissues ( p  < 0.0001). No THBS1 methylation was found in 40 healthy controls, and partial methylation was detected in 3 of 48 patients with chronic non‐atrophic gastritis. The frequency of THBS1  methylation in pairing PPLF and serum from 92 GC patients was 52.2% (48/92) and 58.7% (54/92), respectively. The results of methylated THBS1 in pairing PPLF and serum were similar to those of tumor tissues. Aberrant THBS1 methylation in tumor tissues and pairing PPLF or serum was closely related to peritoneal dissemination, tumor progression, and poor prognosis (all p  < 0.0001). Conclusion: Circulating methylated THBS1 DNAs in PPLF/serum may predict peritoneal dissemination, a potential poor prognostic factor for GC patients. Abstract : Postoperative recurrence of gastric cancer usually occurs in the peritoneum, and peritoneal dissemination and recurrence are the main causes of poor prognosis. Therefore, it is very necessary to find a biomarker that can predict peritoneal dissemination of gastric cancer cells. Here, we found that THBS1 methylation levels in preoperative serum or peritoneal fluid can accurately predict peritoneal dissemination and suggest a poor prognosis in patients with gastric cancer.